2019
DOI: 10.3390/antibiotics8040164
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacteria of Water Monitor Lizard (Varanus salvator) Are a Potential Source of Antibacterial Compound(s)

Abstract: For the past few decades, there has been limited progress in the development of novel antibacterials. Previously, we postulated that the gut microbiota of animals residing in polluted environments are a forthcoming supply of antibacterials. Among various species, the water monitor lizard is an interesting species that feeds on organic waste and the carcass of wild animals. Gut microbiota of the water monitor lizard were sequestered, identified and cultivated in RPMI-1640 to produce conditioned medium (CM). Nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Epigenetic treatment holds great potential in the treatment of several diseases such as metabolic disorders, cancer, and cardiovascular and neurological diseases [ 4 ]. Furthermore, the ability of the epigenome to be flexible, has enabled scientists to investigate its reversal through designing epigenetic drugs as an approach to ameliorate disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic treatment holds great potential in the treatment of several diseases such as metabolic disorders, cancer, and cardiovascular and neurological diseases [ 4 ]. Furthermore, the ability of the epigenome to be flexible, has enabled scientists to investigate its reversal through designing epigenetic drugs as an approach to ameliorate disease phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, crocodiles have also been reported to possess bioactive peptides that revealed anti-oxidative, anti-inflammatory, anti-microbial, and anti-cancer attributes [ 1 , 2 ]. In this regard, we have recently postulated and shown that the sera and gut bacteria of animals such as crocodiles ( Crocodylus palustris and Crocodylus porosus) and water monitor lizard ( Varanus salvator ), tortoise ( Cuora amboinensis kamaroma ) as well as other species that reside in polluted environments depict anti-tumour and antibacterial activities and may contribute to the longevity and hardiness of these species [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we have isolated gut bacteria from animals/pests and tested their conditioned media (extracts) against multi-drug resistant Gram-negative and Gram-positive bacteria [9,15]. Bioactive molecules were identified (see Supplementary Figures S1-S5) [9,23] and out of which a few selected compounds were obtained from Sigma Aldrich and tested for their antibacterial properties. The results revealed that all three compounds exhibited significant bactericidal activities (Figure 1a,b) (P < 0.05, using student's t-test, two-tailed distribution).…”
Section: Curcumenol L-homotyrosine and Docosanedioic Acid Showed Sigmentioning
confidence: 99%
“…Bacterial species used in this study include multi-drug resistant Pseudomonas aeruginosa (ATCC 10145) and Streptococcus pyogenes (ATCC 49399) and grown overnight at 37 • C and maintained aerobically prior to experimentations as previously described [23].…”
Section: Bacterial Culturesmentioning
confidence: 99%
“…Reptiles also possess greater longevity than similar‐sized land mammals, for example crocodiles are long‐lived reptiles sometimes living up to 100 years, advocating that we ought to learn from these species. Given that most of the immune system is thought to reside in the gut, accordingly, we speculated that the gut microbiome of reptiles most likely contributes to their robust immune system, their ability to thwart infectious diseases, cancer, and in some cases display limited or negligible senescence (Akbar, Siddiqui, Sagathevan, Iqbal, et al, 2019; Akbar, Siddiqui, Sagathevan, et al, 2020; Jeyamogan et al, 2019, 2020; Siddiqui et al, 2021; Wiertsema et al, 2021). Currently, the gut microbiome is accepted to play a crucial role on the health of the host, and a surfeit of studies have depicted that the gut microbiome may provide protection against neurodevelopment disorders, as well as cancer, among other diseases (Lee et al, 2021; Mohajeri et al, 2018; Siddiqui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%